Resilience strategies in response to the impact of covid-19 pandemic : the case of selected families in Polokwane, South Africa - Ramoshaba, Dillo Justin (My University, 2024)
The Coronavirus Disease of 2019 (COVID-19) pandemic came as another challenge in South Africa’s history, resulting in the disorientation of some families. Several studies show that the pandemic negatively affected the lives of many individuals wherein some lost their jobs whilst others experienced mental health issues which affected their family functioning. It is from this background that this study sought to explore the resilience strategies that were employed in response to the impact of the COVID-19 pandemic by the selected families in Polokwane. Eight (8) COVID-19-affected families in Polokwane were used as a case study wherein convenient and snowball sampling techniques were triangulated to select the respondents in the study. Twenty four (24) respondents (12 Males and 12 Females) participated in this study. Data in this study were collected through semi-structured interviews and analysed thematically with the help of Nvivo software for thematic formulation. A triangulation of theories was used in this study wherein the Vulnerability theory was used to analyse how individuals and families became vulnerable to the COVID-19 pandemic. In addition, the Coping theory was used to explore the coping strategies of families, and lastly, the Resilience theory was adopted interpret how families bounced back from the hardships that they faced as a result of the emergence of the COVID-19 pandemic in Polokwane. The findings reveal that families in Polokwane experienced changes in their family relationships such as loss of family bonds as a result of the COVID-19 lockdown. Domestic violence, which was also instigated by home confinement and alcohol consumption was revealed as one of the factors which contributed to family disorientation. Besides, job loss was also revealed as one of the factors that caused disorientation in some families in Polokwane. The findings of the study further revealed that some individuals within some families experienced mental health issues which were instigated by emotional and behavioural changes, fear and being in quarantine and isolation. Additionally, the findings revealed smoking, alcohol consumption, prayer, family and peer support and government services such as social grants and food parcels as resilience strategies that the families in Polokwane employed in their response to the impact of the COVID-19 pandemic. In light of the above findings, in this study, a family support framework amid natural disasters in South Africa is suggested. Recommendations based on the findings and conclusions of the study are also provided.
Thesis (Ph.D. (Social work)) -- University of Limpopo, 2024
Keywords: Coronavirus Disease; (COVID-19) pandemic; Resilience strategies; Disaster relief; Cope; COVID-19 Pandemic, 2020-2023; Resilience